Root coverage procedures improve patient aesthetics. A systematic review and Bayesian network meta‐analysis. (16th September 2016) - Cairo, Francesco; Pagliaro, Umberto; Buti, Jacopo; Baccini, Michela; Graziani, Filippo; Tonelli, Paolo; Pagavino, Gabriella; Tonetti, Maurizio S.
Abstract: Background: The aim of this study was to perform a systematic review (SR) of randomized controlled trials (RCTs) to explore if periodontal plastic surgery procedures for the treatment of single and multiple gingival recessions (Rec) may improve aesthetics at patient and professional levels. Material and Methods: In order to combine evidence from direct and indirect comparisons by different trials a Bayesian network meta‐analysis (BNM) was planned. A literature search on PubMed, Cochrane libraries, EMBASE, and hand‐searched journals until January 2016 was conducted to identify RCTs presenting aesthetic outcomes after root coverage using standardized evaluations at patient and professional level. Results: A total of 16 RCTs were selected in the SR; three RTCs presenting professional aesthetic evaluation with Root coverage Aesthetic Score (RES) and three showing final self‐perception using the Visual Analogue Scale (VAS Est) could be included in a BNM model. Coronally Advanced Flap plus Connective Tissue Graft (CAF + CTG) and CAF + Acellular Dermal Matrix (ADM) and Autologous Fibroblasts (AF) were associated with the best RES outcomes (best probability = 24% and 64%, respectively), while CAF + CTG and CAF + CTG + Enamel matrix Derivatives (EMD) obtained highest values of VAS Est score (best probability = 44% and 26%, respectively). Conclusions: Periodontal Plastic Surgery (PPS) techniques applying grafts underneath CAF with or without the adding of EMD are associated with improved aesthetics assessed by final patient perception and RES as professional evaluation system.